2015
DOI: 10.2169/internalmedicine.54.3034
|View full text |Cite
|
Sign up to set email alerts
|

Biliary Tract Infection or Colonization with Elizabethkingia meningoseptica after Endoscopic Procedures Involving the Biliary Tract

Abstract: Objective This study was performed to investigate the clinical significance of detecting Elizabethkingia meningoseptica in the bile. Methods We herein report a case series of biliary colonization or infection with E. meningoseptica. Twenty patients with E. meningoseptica recovered from the bile were treated at a 4,300-bed teaching hospital in China between January 2009 and December 2012. The clinical information for the cases of E. meningoseptica recovered from the bile and the microbiological data of the E. m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 20 publications
0
4
0
Order By: Relevance
“…The literature showed that E. meningoseptica was detected in six species (humans, pigs, dogs, birds, insects, and corn) and was reported on ve continents (Asia, Europe, America, Africa, and Oceania), of which Asia had the most reports, followed by Europe and America (Table 1). There were 32 epidemiological investigation reports related to E. meningoseptica infection, which included 366 infected people; the overall mortality rate of patients with E. meningoseptica infection was > 20%, and the highest mortality rate was 63.20% (Table 2) [5][6][7][8][9][10][11][12][13][14][15][16][17][18]. proportion, with 48 cases (52%) in total, followed by elderly patients (aged > 65 years), with 28 cases (30%) (Fig.…”
Section: Global Epidemiological Characteristics Of E Meningosepticamentioning
confidence: 99%
“…The literature showed that E. meningoseptica was detected in six species (humans, pigs, dogs, birds, insects, and corn) and was reported on ve continents (Asia, Europe, America, Africa, and Oceania), of which Asia had the most reports, followed by Europe and America (Table 1). There were 32 epidemiological investigation reports related to E. meningoseptica infection, which included 366 infected people; the overall mortality rate of patients with E. meningoseptica infection was > 20%, and the highest mortality rate was 63.20% (Table 2) [5][6][7][8][9][10][11][12][13][14][15][16][17][18]. proportion, with 48 cases (52%) in total, followed by elderly patients (aged > 65 years), with 28 cases (30%) (Fig.…”
Section: Global Epidemiological Characteristics Of E Meningosepticamentioning
confidence: 99%
“…Although it rarely causes biliary tract infection, cholangitis due to E. meningoseptica is generally associated with a favourable prognosis. 3 Here, we report the case of an elderly lady who developed cholangitis due to E. meningoseptica following biliary stent placement and died subsequently because of septic shock.…”
Section: Introductionmentioning
confidence: 97%
“…While healthy individuals rarely contract E. meningoseptica infections or diseases, there has been an increasing number of reports linking this bacterium to life-threatening infections in immunocompromised individuals. It has been associated with severe meningitis (particularly neonatal meningitis) ( 5 11 ), bacteremia ( 12 17 ), respiratory infection ( 18 , 19 ), urinary tract infection ( 20 ), sepsis ( 21 , 22 ), eye infections ( 23 26 ), biliary tract infections ( 27 , 28 ) and has emerged as a significant public health concern. Furthermore, recent studies have described nosocomial outbreaks associated with E. meningoseptica ( 5 , 6 , 21 , 29 31 ).…”
Section: Introductionmentioning
confidence: 99%